Reduction of Fe(II), Zn(II) and Cd(II) using rice husk - Nurul Nadia, Samin (2012)
Adsorption method is simple and relatively cost-effective, thus has been widely used.Several materials are derived from natural resources, plant wastes or industrial byproducts. Rice husk is a byproduct of the rice milling industry. It was chosen because of its granular structure,chemical stability and its local availability at very low cost and there is no need to regenerate them due to their low production costs. The purpose of this research is reduction of Fe(II),Zn(II) and Cd(II) using Rice Husk.Besides that,this research is also to investigate the potential of rice husk for reduction of Fe(II),Zn(II)and Cd(II) heavy metal ions by the effect variation of contact time,adsorbent dosage and initial concentration.The adsorbent was prepared by collecting the rice husk,dried and ground the rice husk using grinder and mechanical sieve to specify the adsorbent to certain size. 0.5g of rice husk as adsorbent with 50 ml adsorbate was kept constant for this experiment using 100 mg/L for initial concentration then there were placed on orbital shaker, operated at 150 rpm by varied time in 10 minutes to 120 minutes.For variation adsorbent dosage, the solution was set for different of dosage from 0.3 until 1.8 grams then placed on orbital shaker at constant 150 rpm and 25’C.Initial concentration from 10 until 125 mg/L was used with adsorbent samples in optimum weight and time then placed on orbital shaker at constant 150 rpm and 25’C.Adsorption process using rice husk was found to be suitable at initial concentration on 100 mg/L.Kinetic studies were conducted where both pseudo-first order and pseudo-second order yield value of R2 from 0.885 to 0.961and from 0.955 to 0.999 for each order. Adsorption isotherms were described by both Langmuir and Freundlich isotherms.Langmuir equation was found to represent the equilibrium data for adsorption of Fe(II), Zn(II) and Cd(II) using rice husk ( 0.942 < R2< 0.981),and the maximum adsorption capacity was highest for Cd(II) with 1.4793 mg/g.